Land Ownership and Urban Growth: The Experience of Two Quebec Towns, 1840-1914 - Rudin, Ronald (Urban History Review / Revue d'histoire urbaine, 1979)
The Quebec towns of Sherbrooke and Sorel both offered certain attractions for economic development in 1840. Sorel was located at the junction of two major rivers, while Sherbrooke offered considerable water power to industry. Nevertheless, between 1840 and 1914 Sherbrooke grew much more rapidly than Sorel. The nature of land ownership was an important factor in differentiating the experiences of the two towns. Sorel's most valuable lands were tied up by a succession of government agencies, while the best lands in Sherbrooke were owned by a private land company eager to encourage development.